2019
DOI: 10.18203/2320-6012.ijrms20191306
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gestational diabetes mellitus and its relationship with various risk factors in a tertiary care hospital in West Bengal with special reference to tribal population, India

Abstract: Background: Gestational diabetes mellitus (GDM) is the most common medical complication and metabolic disorder of pregnancy. The aim and objective of this study was to determine the prevalence of GDM and its relationship with various risk factors with special reference to tribal population.Methods: The study was done in 200 patients between 24 and 28 weeks of gestation, attending antenatal outdoor in a tertiary care hospital of West Bengal.  These patients were given 75gm oral glucose irrespective of the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…As a result, the association between smoking habits and the prevalence of GDM should be researched further. The current study contradicted several studies that reported BMI as a risk factor for GDM, although 38.6% of pregnant women with a BMI greater than 25.0kg/m2 had GDM (Sharma et al, 2019). BMI has a strong positive association with the prevalence of GDM, and more than 64% of obese women develop GDM (Muche et al, 2019;Gracelyn & Saranya, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…As a result, the association between smoking habits and the prevalence of GDM should be researched further. The current study contradicted several studies that reported BMI as a risk factor for GDM, although 38.6% of pregnant women with a BMI greater than 25.0kg/m2 had GDM (Sharma et al, 2019). BMI has a strong positive association with the prevalence of GDM, and more than 64% of obese women develop GDM (Muche et al, 2019;Gracelyn & Saranya, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…Hence, the prevalence of GDM in tribal population in this study was 12.12% and 10.44% in non-tribal population. The prevalence of GDM in tribal population was found to be 14.63%, while it is 10.06% in non-tribal population as per study by Sharma et al, 9 which was consistent with our study. The mean age of the study population without GDM was 25.75±4.2 years and for population with GDM was 29.55±3.96.…”
Section: Discussionsupporting
confidence: 92%
“… Gestational diabetes mellitus (GDM): the diagnosis of gestational diabetes mellitus was made, when 75 gm of glucose load and measurement of blood sugar level after 2 hours, ≥140-199 mg/dl [ 8 , 12 , 21 ] Gestational age (GA) is the age of the fetus counting from the time of fertilization [ 22 ] Parity is the number of live-born children a woman has delivered Primipara: those who gave birth only once Multipara: those who gave birth above one time Grand-multi: those who gave birth above five times (4) Dietary diversity: it was tested by the Food and Nutrition Technical Assistance (FANTA) 2016 edition of the minimum dietary diversity measurement tool of a woman using a 24 h food recall process. A list of ten food groups was issued (starchy staples, nuts and seeds, pulses, dairy, meat, eggs, poultry and fish, dark green leafy vegetables, other vitamin-A rich fruits and vegetables, other vegetables, and other fruits).…”
Section: Methodsmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM): the diagnosis of gestational diabetes mellitus was made, when 75 gm of glucose load and measurement of blood sugar level after 2 hours, ≥140-199 mg/dl [ 8 , 12 , 21 ]…”
Section: Methodsmentioning
confidence: 99%